Preharvest Application of Exogenous 2,4-Epibrassinolide and Melatonin Enhances the Maturity and Flue-Cured Quality of Tobacco Leaves - Kesu Wei; Jiayi Tang; Lei Yang; Shaopeng Chen; Zhijun Cheng; Yijun Yang; Chen Xu; Shengjiang Wu; Yuhang Zhao; Hongmei Di; Ling Li; Dongyang Sun; et al. (Plants)
Tobacco (Nicotiana tabacum) is a globally cultivated crop, with its quality closely associated with the color and chemical composition of cured tobacco leaves. In this experiment, the effects of spraying exogenous 2, 4-epibrassinolide (EBR) and melatonin (MT) on the development of tobacco leaves at maturity stage and the quality after curing were investigated. Both EBR and MT treatments significantly enhanced the appearance quality of tobacco leaves at the stem-drying stage. Following preharvest applications, the sugar-to-alkali ratio and potassium content increased, while the contents of starch, total alkaloids, and proteins decreased. The levels of conventional chemical components were improved, enhancing the overall coordination of the tobacco. Transcriptome analysis revealed that EBR treatment down-regulated the chlorophyll biosynthetic genes hemA, MgPEC, and ChlD, while up-regulating the chlorophyll degradation genes CHL2, SGR, and PAOs. Similarly, MT treatment down-regulated the chlorophyll biosynthetic genes FC2 and MgPEC and up-regulated the degradation genes CHL2 and SGR, thus promoting chlorophyll degradation. Furthermore, in the downstream carotenoid biosynthetic pathway, both EBR and MT treatments regulated abscisic acid-related genes, with NCEDs being up-regulated and CYP707A1s down-regulated, thereby promoting the leaf ripening. Metabolomics analysis indicated that EBR treatment primarily regulated alkaloids, terpenoids, and flavonoids, while MT treatment mainly affected flavonoids. Both treatments also reduced the accumulation of the harmful substance aristolochic acid B. Comprehensive evaluations of appearance quality, physiological parameters, transcriptome, and metabolomics analyses demonstrated that exogenous spraying of EBR and MT treatments improved the maturity and quality of cured tobacco leaves, with EBR treatment exhibiting a greater effect than MT treatment.